2020
DOI: 10.1002/imhj.21904
|View full text |Cite
|
Sign up to set email alerts
|

Higher maternal reflective functioning is associated with toddlers’ adaptive emotion regulation

Abstract: Parental reflective functioning (RF), the ability to consider the child's behavior as a function of mental states (cognitions, emotions), is theorized to promote emotion regulation in children via its positive impact on parenting sensitivity. Using a sample of mothers and toddlers (N = 151 dyads; 41% Latinx; 54% girls; MAge = 21 months; SDAge = 2.5 months), we measured mothers’ self‐reported RF (high RF = low certainty/high interest–curiosity/low prementalizing), toddlers’ distress during a standardized challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…If a mother with low PRF does not recognize or misinterprets her child’s inner feelings and moods, she may ignore her child’s needs, which may result in feelings of neglect, helplessness, mistrust, and anxiety, and consequently may lead to internalizing problems in the child [ 20 , 44 ]. In other words, continuous mentalization and reflection upon underlying causes of behavior is crucial for developing emotion regulation, self-regulation, and a sense of security in children [ 45 , 46 ], which in turn help decrease internalizing and externalizing problems [ 47 , 48 ]. Previous research has shown similar results, indicating significant relationships between indices of PRF and internalizing and externalizing problems in preschoolers and school-aged children [ 21 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…If a mother with low PRF does not recognize or misinterprets her child’s inner feelings and moods, she may ignore her child’s needs, which may result in feelings of neglect, helplessness, mistrust, and anxiety, and consequently may lead to internalizing problems in the child [ 20 , 44 ]. In other words, continuous mentalization and reflection upon underlying causes of behavior is crucial for developing emotion regulation, self-regulation, and a sense of security in children [ 45 , 46 ], which in turn help decrease internalizing and externalizing problems [ 47 , 48 ]. Previous research has shown similar results, indicating significant relationships between indices of PRF and internalizing and externalizing problems in preschoolers and school-aged children [ 21 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a variety of family-based contextual factors have been identified as predictors of SoE development in early life. These include the family’s overall emotional climate as reflected by factors such as parents' emotional well-being and coparenting relationships (Gallegos et al, 2017), and indicators of parenting quality including sensitivity, mind-mindedness and reflective functioning, and infant–parent attachment relationships (Borelli et al, 2021; Morris et al, 2017), to name but a few. A construct less often examined in studies of infants and young children, but one that appears to play an important role in the quality of family life and child functioning, is household chaos (Deater-Deckard et al, 2009; Whitesell et al, 2015).…”
mentioning
confidence: 99%
“…Importantly, young children presenting with externalizing and internalizing disorders may be adapting to parental behavior in order to sustain the attachment relationship, even if costly to their psychosocial development ( Sroufe, 2009 ; Borelli et al, 2020 ). Mothers who are experiencing intrusive thoughts while interacting with their infant may demonstrate behaviors that are disruptive to the infants’ affective communication, such as dissociation, aversive hostility, or withdrawal ( Lyons-Ruth et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a secure mother–infant attachment not only promotes resiliency, but also protects against such behavioral issues ( Letourneau, 1997 ; Edwards et al, 2006 ; Cyr et al, 2010 ; Riva Crugnola et al, 2014 ). Higher parental cognitive empathy and reflective functioning, both of which measure the capacity to perceive and understand the emotional states of others, are connected to emotion regulation and social competence in children ( Wong et al, 2017 ; Borelli et al, 2020 ). Furthermore, higher frequency of shared pleasure moments in early childhood between mother and child have been shown to lower the likelihood of emotional/behavioral problems in children and moderate the possible negative effects of parental psychopathology on the development of children’s emotion regulation abilities ( Mäntymaa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%